NONO, SFPQ, and PSPC1 promote telomerase recruitment to the telomere - Alexander P. Sobinoff; Jadon K. Wells; Maurice Chow; Christopher B. Nelson; Xinyi Wu; Scott B. Cohen; Yu Heng Lau; Tracy M. Bryan; Archa Fox; Hilda A. Pickett (Nature Communications)
Abstract Telomerase is a ribonucleoprotein enzyme that maintains telomeric repeats on chromosome ends in continuously dividing cells. Telomere maintenance via telomerase is dependent on the correct assembly of the enzyme complex, complex stabilization by associated cofactors, and effective recruitment to the telomere. Here, we show that telomerase is regulated in each of these processes by the Drosophila behaviour/human splicing (DBHS) family of RNA/DNA binding proteins (NONO, SFPQ and PSPC1). The DBHS proteins associate with catalytically active telomerase through the hTR RNA template component. Cells lacking the DBHS proteins display telomerase retention in nuclear Cajal bodies and impaired telomerase recruitment to the telomere, with NONO and PSPC1 depletion culminating in progressive telomere shortening in several cell lines, with the exception of long-term NONO depletion in 293 and 293T. Our results reveal the DBHS protein family as components of the telomerase trafficking machinery integral to telomere maintenance.